2020
DOI: 10.1007/s00702-020-02189-9
|View full text |Cite|
|
Sign up to set email alerts
|

9-Methyl-β-carboline inhibits monoamine oxidase activity and stimulates the expression of neurotrophic factors by astrocytes

Abstract: β-Carbolines (BC) are pyridoindoles, which can be found in various exogenous and endogenous sources. Recent studies revealed neurostimulative, neuroprotective, neuroregenerative and anti-inflammatory effects of 9-methyl-BC (9-Me-BC). Additionally, 9-me-BC increased neurite outgrowth of dopaminergic neurons independent of dopamine uptake into these neurons. In this study, the role of astrocytes in neurostimulative, neuroregenerative and neuroprotective properties of 9-me-BC was further explored. 9-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…These results may be considered an effect of the positive impact of a diet enriched with β-carbolines on aged individuals. Some literature data reported that 9-me-BC lowered the content of α-synuclein in the primary dopaminergic cell cultures [ 27 ], as well as stimulated the gene expression of several important neurotrophic factors like Artn, Bdnf, Egln1, Tgfb2, and Ncam1, which are known to stimulate neurite outgrowth and exhibit neuroprotective and neuroregenerative properties to dopaminergic neurons [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results may be considered an effect of the positive impact of a diet enriched with β-carbolines on aged individuals. Some literature data reported that 9-me-BC lowered the content of α-synuclein in the primary dopaminergic cell cultures [ 27 ], as well as stimulated the gene expression of several important neurotrophic factors like Artn, Bdnf, Egln1, Tgfb2, and Ncam1, which are known to stimulate neurite outgrowth and exhibit neuroprotective and neuroregenerative properties to dopaminergic neurons [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although past research has determined that hyperactivated astrocytes form glial scars after SCI, preventing nerve fibers from repairing and inhibiting neuronal axon growth ( Okada et al, 2018 ). With the deepening of related research, many researchers have found that astrocytes can secrete neurotrophic factors and other neuronal support substances to endorse the repair of damaged neurons ( Keller et al, 2020 ; Linnerbauer and Rothhammer, 2020 ). Furthermore, the degree of neuronal repair and its functional recovery is largely dependent on the growth of nascent axons.…”
Section: Introductionmentioning
confidence: 99%